Global guideline for the diagnosis and management of the endemic mycoses: an initiative of the European Confederation of Medical Mycology in cooperation with the International Society for Human and Animal Mycology. Issue 12 (December 2021) - Thompson, George R; Le, Thuy; Chindamporn, Ariya; Kauffman, Carol A; Alastruey-Izquierdo, Ana; Ampel, Neil M; Andes, David R; Armstrong-James, Darius; Ayanlowo, Olusola; Baddley, John W; Barker, Bridget M; Lopes Bezerra, Leila; et al.
Summary: The global burden of the endemic mycoses (blastomycosis, coccidioidomycosis, emergomycosis, histoplasmosis, paracoccidioidomycosis, sporotrichosis, and talaromycosis) continues to rise yearly and these infectious diseases remain a leading cause of patient morbidity and mortality worldwide. Management of the associated pathogens requires a thorough understanding of the epidemiology, risk factors, diagnostic methods and performance characteristics in different patient populations, and treatment options unique to each infection. Guidance on the management of these infections has the potential to improve prognosis. The recommendations outlined in this Review are part of the "One World, One Guideline" initiative of the European Confederation of Medical Mycology. Experts from 23 countries contributed to the development of these guidelines. The aim of this Review is to provide an up-to-date consensus and practical guidance in clinical decision making, by engaging physicians and scientists involved in various aspects of clinical management.